Climate change and human security implications for humanitarian, development, disaster and climate risk management in Mozambique - ODI Global; Center for Climate and Security (CCS) (2024)
As part of the project ‘Catalyzing cohesive action on climate and security: bridging silos for enhanced humanitarian action’ for USAID’s Bureau of Humanitarian Assistance, ODI, the Center for Climate and Security (CCS) and the CGIAR FOCUS Climate Security Team at the Alliance of Bioversity International and International Center for Tropical Agriculture (CIAT) hosted a workshop on 4–5 March 2024 in Maputo, Mozambique, to discuss challenges and opportunities across climate adaptation, peace and security, development, and humanitarian aid to support climate-resilient development in Mozambique. Participants comprised representatives from the Government of Mozambique, donor agencies, and international and national non-governmental organisations (NGOs) currently working on climate, peace and security, development and humanitarian programming. Discussions focused on the challenges and opportunities to better link, layer and sequence interventions, to increase access to finance, and to catalyse more cohesive and coordinated action.